The Influence of Government Funding on Advancing Digital Transformation within the Arts and Cultural Landscape in Indonesia - Ari Wibowo (International Journal of Education and Literature, 2023)
This research paper focuses on exploring the influence of government funding on advancing digital transformation within the arts and cultural landscape in Indonesia. The primary goal of this study is to investigate the impact of government funding initiatives on catalyzing digital transformation within this dynamic domain. Digital transformation has become a critical force in shaping the arts and cultural sector, revolutionizing the creation, accessibility, and dissemination of artistic expressions. While several studies have examined digital transformation and government funding in various contexts, limited research has specifically focused on the influence of government funding on advancing digital transformation within the arts and cultural landscape in Indonesia. The problem statement revolves around understanding the extent to which government funding initiatives impact the advancement of digital transformation in the arts and cultural sector in Indonesia. The research questions include exploring the key factors shaping the relationship between government funding and digital transformation, as well as understanding the challenges and opportunities associated with these initiatives. This study employs a qualitative research methodology, specifically relying on secondary data sources such as academic journals, research papers, books, government reports, and relevant documents. The findings of this study provide valuable insights into the influence of government funding on advancing digital transformation within the arts and cultural landscape in Indonesia. The analysis reveals key factors shaping the relationship between government funding and digital transformation, highlighting challenges and opportunities for future development. This study has implications for policymakers, practitioners, and researchers, guiding strategic decision-making and policy formulation to drive the advancement of digital practices within the arts and cultural landscape in Indonesia.